Ochrona dziedzictwa narodowego przed szkodliwym działaniem mikrobiologicznym. Warunki i środki zapobiegawcze - Bangrowska, Agnieszka (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
This article aims to present the physicochemical methods and chemical agents used to com-bat microorganisms in library collections as well as in library rooms. Based on an analysis of documentation available at various library centres, the methods and chemicals used to destroy fungi and moulds were compared. The standard storage conditions of library collections were used. Library collections from different sources can be attacked by microorganisms because they are almost entirely composed of organic materials, forming nutritional matter for those organisms. Environmental supervision is only one of many ways to prevent and ensure proper book storage conditions, but it is not a suitable method for fighting bacteria, fungi, mould, etc. The ways and methods of library collections’ disinfection should be considered very broadly. Disinfection of the collection itself is not enough; this must be combined with disinfection of the storerooms and additionally the removal of all potential sources of infestation. Emphasis should be placed on the implementation of modern methods of destroying microorganisms which, of course, will not harm humans but will prolong the life of library collections. Moreover, libraries and warehouses should be equipped with appropriate equipment to maintain suitable climatic conditions.